SCIENTIFIC AND METHODOLOGICAL BASES OF ECOLOGICAL EDUCATION OF SCHOOLCHILDREN - Yusupov Ibragim Mirsaydalievich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article is devoted to the methodological issues of environmental education of primary school students. The article also highlights the concept of environmental education and its essence, the role of environmental education in primary school age, the relationship between nature and man, environmental skills and conservation skills, types of natural resources, flora and fauna, humane attitude towards nature, issues of environmental education. such as the methodological basis of the transmission are also widely reported.